2011
DOI: 10.1111/j.1582-4934.2011.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Npp1 promotes atherosclerosis in ApoE knockout mice

Abstract: Objective Ecto-Nucleotide Pyrophosphatase/Phosphodiesterase 1 (NPP1) generates inorganic pyrophosphate (PPi), a physiologic inhibitor of hydroxyapatite deposition. In a previous study, we found NPP1 expression to be inversely correlated with the degree of atherosclerotic plaque calcification. Moreover, function-impairing mutations of ENPP1, the gene encoding for NPP1, are associated with severe, artery tunica media calcification and myointimal hyperplasia with infantile onset in humans. NPP1 and PPi have the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…35,36 Lower levels of PP i are the main cause of the arterial calcification in patients with calcification of infancy and in the respective mouse models of defective ENPP1. [36][37][38] In contrast, increased levels of PP i are known to inhibit vascular calcification. 39 The ENPP1 K173Q mutation identified in this study has previously been shown to affect intracellular ENPP1 activity and serum ENPP1 enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Lower levels of PP i are the main cause of the arterial calcification in patients with calcification of infancy and in the respective mouse models of defective ENPP1. [36][37][38] In contrast, increased levels of PP i are known to inhibit vascular calcification. 39 The ENPP1 K173Q mutation identified in this study has previously been shown to affect intracellular ENPP1 activity and serum ENPP1 enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…3 At the same time, P i can serve as a pro-mineralization factor, particularly in the context of increased inorganic phosphate/ pyrophosphate (P i /PP i ) ratio. 4 In 2004, 3 research groups independently generated knock out mice by targeted disruption of the mouse Nt5e, the gene encoding CD73. [5][6][7] These mice were subsequently characterized to show altered thromboregulation and augmented vascular inflammatory response, lack of CD73 was shown to promote arteriogenesis, and the Nt5e ¡/¡ mice manifested with fulminant vascular leakage during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Increased TNAP activity could certainly clear pyrophosphate generated by ENPP1 and might mimic outcomes of the more severe form of vascular calcification noted in generalized arterial calcification of infancy; the latter characterized by mutations in ENPP1 and low generation rates of pyrophosphate ab initio [3]. Although deletion of Enpp1 in mice models disease in infancy with soft tissue and arterial medial calcification associated with ectopic osteochondral differentiation [16][17][18], it seems that Cd73 deletion in mice does not result in similar phenotypes [16,[18][19][20]. The authors are to be congratulated on this important clinical discovery.…”
Section: Important Insights Possible Caveats and Future Directions Fmentioning
confidence: 99%